A propósito de la teología apofática. Algunos apuntamientos semánticos - Moya Bedoya, Juan Diego M. (Universidad de Costa Rica, 2017)
In this paper, Professor Moya B. exposes and analyzes some issues related to apophatic theology, in particular its fundamental pretension and the legitimacy of some of its statements. Identically, the author methodically exposes some inconsistencies of apophatic theology. The article has been prepared in order to celebrate the publication of Professor Edgar Ulloa-Molina’s new book, a text that concerns some metaphysical issues that subtend the architectural reform of Saint Denis Royal Abbey’s Church.